High‐Latitude Ionospheric Electrodynamics During STEVE and Non‐STEVE Substorm Events. Issue 4 (15th April 2023) - Svaldi, V.; Matsuo, T.; Kilcommons, L.; Gallardo‐Lacourt, B.
Abstract: Previous studies have shown that Strong Thermal Emission Velocity Enhancement (STEVE) events occur at the end of a prolonged substorm expansion phase. However, the connection between STEVE occurrence and substorms and the global high‐latitude ionospheric electrodynamics associated with the development of STEVE and non‐STEVE substorms are not yet well understood. The focus of this paper is to identify electrodynamics features that are unique to STEVE events through a comprehensive analysis of ionospheric convection patterns estimated from SuperDARN plasma drift and ground‐based magnetometer data using the Assimilative Mapping of Geospace Observations (AMGeO) procedure. Results from AMGeO are further analyzed using principal component analysis and superposed epoch analysis for 32 STEVE and 32 non‐STEVE substorm events. The analysis shows that the magnitude of cross‐polar cap potential drop is generally greater for STEVE events. In contrast to non‐STEVE substorms, the majority of STEVE events investigated are accompanied by with a pronounced extension of the dawn‐cell into the pre‐midnight subauroral latitudes, reminiscent of the Harang reversal convection feature where the eastward electrojet overlaps with the westward electrojet, which tends to prolong over substorm expansion and recovery phases. This is consistent with the presence of an enhanced subauroral electric field confirmed by previous STEVE studies. The global and localized features of high‐latitude ionospheric convection associated with optical STEVE events characterized in this paper provide important insights into cross‐scale magnetosphere‐ionosphere coupling mechanisms that differentiate STEVE events from non‐STEVE substorm events. Plain Language Summary: In 2016, citizen observers introduced a mysterious subauroral phenomenon called Strong Thermal Emission Velocity Enhancement (STEVE) to the scientific community. STEVE events are characterized by the presence of a thin and bright purple emission located closer to the horizon than the typical aurora. The focus of this paper is to quantify characteristic features of the global ionosphere during STEVE events, and to investigate their relationship to related phenomena known as substorms using a newly developed data science tool named Assimilative Mapping of Geospace Observation (AMGeO). In this study, using AMGeO, we analyze large amounts of ground‐based data during 32 STEVE events as well as 32 non‐STEVE substorm events. Findings from the study are helpful to understand differences in the way the magnetosphere is coupled to the ionosphere during STEVE events and non‐STEVE substorms. Key Points: First application of Assimilative Mapping of Geospace Observation on MI coupling focused on global convection patterns for Strong Thermal Emission Velocity Enhancement (STEVE) and non‐STEVE substorms A strong dawn‐cell extending into subauroral pre‐midnight sector and enhanced asymmetry in the both dawn and dusk cells during STEVE events Larger cross‐polar cap potential drop and more prolonged nightside asymmetry found in STEVE events